Amor Eterno : Eleven Lessons in Love - Martin, Patricia Preciado (Book collections on Project MUSE., 2000)
"Through stories that blend songs, letters, and prayers, Patricia Preciado Martin explores the hidden places of the soul and the human longing for amor eterno, eternal love. Forbidden love, enchanted love, and desperate love are just some of the varieties of love that get mixed into this concoction of romance, wit, and instruction. A combination of modern sensibility and folk wisdom, this book tells universal tales of devotion and desire."--Jacket.